2021
DOI: 10.1186/s13040-021-00233-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-TRACK: world and USA SARS-COV-2 testing and COVID-19 tracking

Abstract: Background The COVID-19 pandemic has caused major health and socio-economic disruptions worldwide. Accurate investigation of emerging data is crucial to inform policy makers as they construct viral mitigation strategies. Complications such as variable testing rates and time lags in counting cases, hospitalizations and deaths make it challenging to accurately track and identify true infectious surges from available data, and requires a multi-modal approach that simultaneously considers testing, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Each question is rated as low risk of bias if the study has considered the bias or high risk if the study may be biased, where a score of 1 is given. The overall score summarises the study as low (0-3), moderate (4)(5)(6) or high (7-10) risk of bias.…”
Section: Study Quality Assessment and Data Extractionmentioning
confidence: 99%
“…Each question is rated as low risk of bias if the study has considered the bias or high risk if the study may be biased, where a score of 1 is given. The overall score summarises the study as low (0-3), moderate (4)(5)(6) or high (7-10) risk of bias.…”
Section: Study Quality Assessment and Data Extractionmentioning
confidence: 99%
“…Voluntary and mandated quarantine, ban of mass gatherings and large events, closing schools and workplaces, and isolation of households/regions were some of the measures applied by governments to reduce diseases' mortality [1][2][3][4][5]. Pandemics and epidemics also showed that such diseases can have a significant toll on the economies [1, [3][4][5][6][7]. For this reason, countries and regions have to decide which mitigation measures to implement and when to apply them in order to avoid reaching peaks that would overwhelm healthcare services but also to define measures acting as moderators of the disease negative effects on the economy, a balance that is not easy to reach [1].…”
Section: Introductionmentioning
confidence: 99%
“…From a comprehensive diagnosis perspective, the use of data science and machine learning methods and techniques constitutes an opportunity for research to achieve this purpose. Specifically, open data being shared by reputable organizations allow for almost real-time access to detailed data across the world and enable imperative data collection and analysis to be performed in order to advance with the necessary understanding and decision-making [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although well-done, randomized clinical trials are needed urgently to test potential therapies including HCQ once the pharmacokinetics and pharmacodynamics (PK/PD) of HCQ are fully understood for the identification of an effective and safe therapeutic regimen for treatment of patients, we decided to study the potential mechanism(s) in an animal model, in anticipation of any benefits, if at all, regarding repurposing of HCQ in treating viral infections such as COVID-19 [32][33][34][35][36]. It is known that chloroquine (CQ) inhibits MMPs activity, endothelial hyperpermeability and by doing so it stops the leakage [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. The mechanism(s) of action of CQ or its derivatives are still being worked out because they are not yet fully elucidated [54][55][56].…”
Section: Introductionmentioning
confidence: 99%